ILLOCUTIONARY ACTS IN THE MOVIE MIDWAY (2019): A CULTURAL AND PRAGMATIC PERSPECTIVE - Reinaldy Christian Panduputra; Deden Novan Setiawan Nugraha (Lembaga Penelitian Universitas Pasundan, 2024)
This study observes the illocutionary acts in the film